Hubungan Antara Kadar Hdl Dan Asupan Kalium Dengan Tekanan Darah Pada Penderita Stroke Iskemik Di Instalasi Rawat Jalan Rsud Sukoharjo - Rahmawaty, Wening Fitria (2016)
THE RELATIONSHIP OF HDL LEVEL AND POTASSIUM INTAKE WITH BLOOD PRESSURE IN ISCHEMIC STROKE OUT PATIENTS IN SUKOHARJO GENERAL HOSPITAL. Introduction : Blood pressure can be affected by HDL level and potassium intake. Low HDL level can cause a blockage in the blood vessel walls. It can be caused by the accumulation of LDL that narrows the blood vessel followed by an increase in blood pressure. Furthermore, low potassium intake could also cause blood pressure to increase. Objective : This study aimed to determine the relationship of HDL level and potassium intake with blood pressure in out patients with stroke ischemic in Sukoharjo General Hospital. Methods : This study is an observational research using Cross Sectional method. The number of samples that have been analyzed were 30 respondents, using Consecutive Sampling technique. HDL levels of respondents were obtained from the last laboratory check, blood pressure levels were obtained from medical record books and potassium intake was obtained from Semi Quantitative of Food Frequency Questioner (FFQ). The correlationtest was performed using Rank Spearmen test. Results : The analysis from this study shows that the average of HDL levels is 44,162 ± 7,18 mg/dl and the averange potassium intake is 375,67 ± 137,76 mg/day. There is no correlation between HDL levels and blood pressure in ischemic stroke patients (p=0,185 for systolic and p=0,528 for diastolic) in addition, there is no correlation between potassium intake and blood pressure in ischemic stroke patients (p=0,164 for systolic dan p=0,384 for diastolic). Conclusion : There is no correlation between both HDL level and potassium intake with the blood pressureof ischemic stroke out patients in Sukoharjo general Hospital. The other factor that influences HDL levels to blood pressure was found to be from foods with high fat content, olders, genetic, genre, Keywords : HDL levels, Potassium intake, Blood Pressure, Stroke Ischemic Bibliography : 69: 1996-2015